2015
DOI: 10.1111/jsap.12400
|View full text |Cite
|
Sign up to set email alerts
|

Indications, outcome and complications with axial pattern skin flaps in dogs and cats: 73 cases

Abstract: There is a high complication rate associated with axial pattern flaps but these are usually easily managed and long term outcome is excellent, in either species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(101 citation statements)
references
References 18 publications
4
88
5
1
Order By: Relevance
“…Indications for APFs application included traumatic wounds in the majority of the cats and cutaneous deficits following tumor excision in 3 cats. This finding compares favorably with those of others where traumatic wounds are the most common indication for APF application in cats (Remedios et al, 1991;Trevor, 1992;Bauer and Salisbury, 1995;Field et al, 2015). Reconstruction of skin deficits following mastectomy by using skin fold flaps as in our study was never reported in the literature (Hunt 1995;Hunt et al, 2001).…”
Section: Discussionsupporting
confidence: 37%
See 4 more Smart Citations
“…Indications for APFs application included traumatic wounds in the majority of the cats and cutaneous deficits following tumor excision in 3 cats. This finding compares favorably with those of others where traumatic wounds are the most common indication for APF application in cats (Remedios et al, 1991;Trevor, 1992;Bauer and Salisbury, 1995;Field et al, 2015). Reconstruction of skin deficits following mastectomy by using skin fold flaps as in our study was never reported in the literature (Hunt 1995;Hunt et al, 2001).…”
Section: Discussionsupporting
confidence: 37%
“…Skin flaps are classified as subdermal or random flaps and as axial pattern flaps (APFs). Subdermal flaps receive their blood supply from terminal braches of direct cutaneous vessels whereas APFs include a direct cutaneous artery and vein (Remedios et al, 1989;Remedios et al, 1991;Trevor et al, 1992;Remedios and Fowler, 1995;Bauer and Salisbury, 1995;Lascelles and White, 2001;Anderson et al, 2004;Benzioni et al, 2009;Field et al, 2015). Axial pattern flaps have better perfusion and provide a 50% larger viable area compared to subdermal plexus flaps (Pavletic 1981).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations